O-band to C-band wavelength converter by using four-wave mixing effect in 1310 nm SOA - Awang, Noor Azura; Ahmad, Harith; Latif, Amirah Abdul; Zulkifli, Mohd Zamani; Ghani, Zawajer Abd; Harun, Sulaiman Wadi (Taylor & Francis, 2010)
In this paper we provide a detailed account of an ultra-wideband wavelength converter that shifts from 1310 to 1550 nm using a 1310 nm semiconductor optical amplifier as the nonlinear medium. The experimental approach uses an arrayed waveguide grating (AWG) as a method to slice the broadband output ASE of the 1310 nm SOA into multiple outputs at this O-band. A four-wave mixing technique is used to generate the wavelength conversion, whereby two wavelengths at 1310 nm are used and interact with the 1550 nm continuous wave output from a bismuth-based erbium-doped optical amplifier. In this demonstration, the interacting wavelengths are 1316.75, 1317.47 and 1542.21 nm. The downward conversion wavelengths are 1542.93 and 1541.49 nm, with a converted wavelength spacing of 224 nm.